Progranulin depletion inhibits proliferation via the transforming growth factor beta/SMAD family member 2 signaling axis in Kasumi-1 cells. Issue 1 (January 2021) - Yabe, Kuniaki; Yamamoto, Yasuko; Takemura, Masao; Hara, Takeshi; Tsurumi, Hisashi; Serrero, Ginette; Nabeshima, Toshitaka; Saito, Kuniaki
Abstract: Progranulin is an autocrine growth factor that promotes proliferation, migration, invasion, and chemoresistance of various cancer cells. These mechanisms mainly depend on the protein kinase B (Akt)/mechanistic target of rapamycin (mTOR) pathway. Recent studies have shown that patients with hematopoietic cancer have elevated serum progranulin levels. Thus, the current study aimed to investigate the role of progranulin in hematopoietic cancer cells and how it modulates their proliferation. Both knockdown of progranulin and progranulin neutralizing antibody treatment inhibited proliferation in several human hematopoietic cancer cell lines. Moreover, progranulin depletion not only decreases the phosphorylation level of the Akt/mTOR pathway but also, surprisingly, increases the expression of transforming growth factor-beta (TGF-β) and phosphorylation of mothers against decapentaplegic homolog 2 (SMAD2) in Kasumi-1 cell. Furthermore, LY2109761, an inhibitor of TGF-β receptor type I/II kinase, and TGF-β neutralizing antibody blocked the inhibition of proliferation induced by progranulin depletion. These data provide new insights that progranulin alters cell proliferation via the TGF-β axis and progranulin could be a new therapeutic target for hematopoietic cancers. Abstract : Hematologic neoplasms, Progranulin, Mechanistic target of rapamycin complex 1, Transforming growth factor beta.